A contribution for the identification of indicators for the evaluation of the impact on regional innovation and development of an EU program for university research in the north of Portugal - Maria Estela Ferreira (European Regional Science Association (ERSA), 2016)
A Contribution for the Identification of Indicators for the Evaluation of the Impact on Regional Innovation and Development of an EU Program for University Research in the North of Portugal ABSTRACT Co-financed Programs by the European Union have been with no doubt relevant to contribute to some endeavours of Research and Development in the North of Portugal. This paper intends to provide an insight view on the way some available and/ or feasible indicators can illustrate the results and impact, specifically on Regional Innovation and Development, of an EU Program for Northern Universities, which was devoted to a large spectrum of matters. After an introductory section summarizing some literature mining as relevant to be had in mind while evaluating such Program, the paper briefly describes the three main Universities at stake. That description is followed by a discussion of the relevance of each indicator for the undertaken purposes and, finally, the way the Program could hopefully contribute to Cohesion Policy of the EU, as well as Europe 2020 objectives is stressed.
Keywords: 330; University; Innovation; regional development; Indicators